Symbiotic solutions for colony nutrition: Conserved nitrogen recycling within the bacterial pouch of Tetraponera ants - Mingjie Ma; Qiang Li; Fan Wu; Biru Zhu; Hezhe Lu; Dayong Zhang; Piotr Łukasik; Yi Hu (Proceedings of the National Academy of Sciences, 2025)
While microbial symbioses are fundamental to the nutrition of many animal groups, current paradigms focus on symbiont functions at the host individual level. It remains unclear whether microbial symbioses can sustain colony-level fitness in social insects, whose ecological success depends on nutrient coordination across castes. Here, we investigate the specialized bacterial pouch, a symbiont-containing organ present exclusively in adult workers of Tetraponera nigra -group ants, revealing its crucial role in colony-wide nutrient provisioning. Using a combination of microscopy, amplicon and metagenomic sequencing, and 15 N-urea feeding experiments on four species in the group, we show that its adult-specific pouch-associated microbiota, primarily Tokpelaia , recycle nitrogen from urea and convert it into amino acids which are provisioned to adult workers and developing larvae. Disruption of this nitrogen-recycling symbiosis severely impairs larval growth and overall colony fitness. Our results show how caste-restricted microbial organs can centralize metabolic functions at the colony level, challenging individual-centric paradigms of host–microbe mutualism and providing insights into the pivotal role of microbial symbionts in superorganismal adaptation to nutritional constraints.